2023
DOI: 10.1186/s12931-023-02335-3
|View full text |Cite
|
Sign up to set email alerts
|

Genetic association and causal inference between lung function and venous thromboembolism

Abstract: Background Previous studies have indicated that lower lung function is related to a higher risk of venous thromboembolism (VTE). However, causal inferences may be affected by confounders, coheritability or reverse causality. We aimed to explore the causal association between lung function and VTE. Methods Summary data from public genome-wide association studies (GWAS) for lung function and VTE were obtained from published meta-analysis studies and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Pre-FEV1 and Pre-FVC are considered objective measures of respiratory health ( Zhang et al, 2023 ). As previous studies have demonstrated, reduced microbiota alpha diversity is associated with a worsening of FEV1 and an increased risk of COPD exacerbation ( Erb-Downward et al, 2011 ; Han et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Pre-FEV1 and Pre-FVC are considered objective measures of respiratory health ( Zhang et al, 2023 ). As previous studies have demonstrated, reduced microbiota alpha diversity is associated with a worsening of FEV1 and an increased risk of COPD exacerbation ( Erb-Downward et al, 2011 ; Han et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…An exposure's causal effect was deemed indicative with a nominally significant false discovery rate (FDR < 0.05) in the IVW method, bolstered by consistent results across sensitivity tests. The heterogeneity of instrumental variables was scrutinized using Cochran’s Q test, with significant heterogeneity marked by Q _ p < 0.05 [ 21 ]. Further, the MR pleiotropy residual sum and outlier (MR-PRESSO) test was utilized to identify and adjust for horizontal pleiotropic outliers, refining our effect estimations [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, it is likely that the risk of VTE development in CTD-ILD patients will increase with their increasing lung fibrosis and decreasing DLCO levels [ 84 ]. Lower lung function is also thought to be associated with the development of VTE [ 85 ]. Severe pulmonary fibrosis and decline in lung function can trigger hypoxia in patients, and hypoxia-inducible factor (HIF) will activate the hypoxia signaling pathway, induce platelet activation and regulate the levels of prothrombotic and antithrombotic factors, which can promote thrombosis and even lead to VTE [ 86 ], in which the activation of the nucleotide binding domain, leucine-rich-containing family, pyrin domain containing 3 (NLRP3) inflammatory vesicle complex mediated by HIF-1α plays a key role [ 87 ].…”
Section: Vte Associated With Ctd-ildmentioning
confidence: 99%